AKTIVITAS ANTIBAKTERI EKSTRAK PROPOLIS ALAMI DARI SARANG LEBAH TERHADAP PERTUMBUHAN Enterococcus faecalis - Zaki Mubarak; Santi Chismirina; Hafizah Humairah Daulay (Dentistry Faculty, 2016)
AbstractThe major cause of endodontic failure is the survival of microorganisms in the root filled teeth.Enterococcus faecalis (E. faecalis) is primary bacterium in patients with post treatment endodonticinfection because Ca(OH)2 as a medicament unable to eliminate this bacteria. Propolis, sometimescalled bee glue, is a natural resinous substance collected by honey bee from plants. Propolis containsmany flavonoids and other compounds like tannin, steroid, and essential oil that have antibacterialproperties. This study was aimed to clarify the antibacterial activity of propolis extracts against E.faecalis. In this laboratory experimental study, natural propolis from bee hives was extracted bymaceration method and 96% ethanol solvent. Propolis that had been phytochemicals test, was testedusing Standard Plate Count (SPC) method to know the antibacterial activity it has. Results showed adecrease colony of E. faecalis after treated with various concentrations of propolis extract. The highestquantity of colonies was founded in concentration 20% is 74.7 x 106 CFU / mL and the least quantityof colonies at a concentration 100% is 7.3 x 106 CFU / mL. Conclusion of this study is natural propolisextract from the bee hives showed antibacterial activity against of E. faecalis.Keyword: Endodontic treatment, Enterococcus faecalis, propolis, bee hives